Feedforward postural adjustments before single leg droplanding in subjects with chronic ankle unstability - Sousa, Andreia (2023)
Chronic ankle instability (CAI) involves deregulation of feedforward postural control. But the analysis of feedforward mechanisms, including early and anticipatory postural adjustments, in tasks close to the mechanisms of injury is still missing.